243 Peyronie's Disease in Young Adults: Symptomatic Burden and Clinical Characteristics. (1st May 2022) - Fallara, G; Capogrosso, P; Boeri, L; Cazzaniga, W; Candela, L; Schifano, N; Costa, A; Pozzi, E; Belladelli, F; Cignoli, D; Raffo, M; Matloob, R; et al.
ABSTRACT: Introduction: Peyronie's disease is a benign condition involving the tunica albuginea of the corpora cavernosa of the penis. Objectives: To investigate whether patients' age has an impact in terms of Peyronie's disease (PD) clinical characteristics at presentation. Methods: Data from a group of 110 consecutive patients aged >18 and <70 years with PD and seeking first medical attention at a single andrological tertiary-referral centre, with a complete clinical assessment and who completed the IIEF-15 and PDQ questionnaires were included in the study. Descriptive statistics was used to compare categorical and continuous variables, between young (≤45 years) and old (>45 years) patients at presentation. Linear and logistic regression analyses tested the association between age and PDQ subscales (Pain, Bother and Symptoms) or IIEF-erectile function domain scores (IIEF-EF ≤26), after adjusting for Charlson Comorbidity Index (CCI), Body Mass Index (BMI), duration of PD (as self-reported by the patient) and smoking habit. LOWESS curve was used to graphically investigate the association between age and PDQ pain score. Results: Of 110, 28 (25%) patients were ≤45 years old. Young patients had lower BMI [median (IQR) 24.3 (22.5-25.6) vs. 25.2 (23.7-27.8); p=0.01] and CCI [CCI≥1 in 1 patient (3.6%) vs. 23 (28%); p=0.014) compared to older patients. No differences were found between groups in terms of severity of the penile curvature, PD duration and plaque size. PDQ pain score was 6 (2.8-12.8) for young and 3 (0-8) for older patients (p=0.03). No differences were found in terms of PDQ-symptoms and bother scores, and for IIEF domain scores. At regression analysis, younger age was associated with significant higher PDQ-pain scores at presentation (Coeff 4.45; 95%CI 1.06:7.84; p=0.011). No further associations were observed between age and the other questionnaires. The figure depicts the higher PDQ-pain scores in young compared to older age. Conclusion: Younger PD patients are at higher risk of complaining penile pain at presentation. No difference in terms of symptoms, PD-associated bother, erectile function and other clinical and morphometric characteristics were found between younger and older patients at first assessment. Disclosure: Work supported by industry: no.